ANALISIS SISTEM INFORMASI TATA ARSIP KEPEGAWAIAN DENGAN MENGGUNAKAN METODE PIECES UNTUK MENINGKATKAN KUALITAS PELAYANAN PADA SMPN 2 RANGKASBITUNG - Rina Triyana; Muhamad Sohari (Journal of Research and Publication Innovation, 2025)
Personnel Archive Information System (SIAK) is an important aspect in the effective and efficient management of human resources in an organization.The purpose of this study is to facilitate the work of administrative staff in managing personnel archive data so that it can be resolved more effectively and efficiently. The method used in this study, which uses a quantitative approach by applying pieces analysis based on the results of field studies with data collection using observation and interviews at SMP Negeri 2 Rangkasbitung. The method in the development of the system is to use the waterfall method. In this study has been designed a personnel Archive Information System at SMP Negeri 2 Rangkasbitung, where the information system is built using the programming language PHP (Hypertext Preprocessor) and MySQL as a Database Management System (DBMS). With the personnel Archive Information System is expected to facilitate personnel administration staff in managing data and information concerning the management of personnel archive data at SMP Negeri 2 Rangkasbitung.